Correlation Between High-Sensitivity C-Reactive Protein (HS-CRP) and Severity of Coronary Artery Disease in Diabetic Patients - Muhammad Zahid Ali Raza, Aamir Siddique, Shaoib Ahmed Zia, Tayyab Mohyuddin, Arslan Aslam Chahudhary, Faiza Altaf (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Coronary artery disease (CAD) is a major cause of morbidity and mortality in patients with type 2 diabetes mellitus (T2DM). Systemic inflammation, as measured by high-sensitivity C-reactive protein (hs-CRP), has been implicated in the pathogenesis of atherosclerosis, yet its correlation with angiographic CAD severity in diabetic patients remains underexplored. Objective: To assess the relationship between serum hs-CRP levels and the angiographic severity of CAD in patients with T2DM and evaluate the associated clinical and biochemical risk factors. Methods: This cross-sectional study included 100 patients with type 2 diabetes mellitus (T2DM), aged between 40 and 75 years, who underwent coronary angiography for suspected coronary artery disease (CAD). Based on angiographic findings, patients were categorized into three groups according to disease severity: mild, moderate, and severe CAD. Clinical data, including age, gender, duration of diabetes, hypertension status, and body mass index (BMI), were systematically recorded. Laboratory investigations comprised high-sensitivity C-reactive protein (hs-CRP), fasting blood glucose, glycated hemoglobin (HbA1c), complete lipid profile, and serum creatinine. The association between hs-CRP levels and CAD severity was evaluated using IBM SPSS version 25.0, with a p-value of <0.05 considered statistically significant. Results: Serum hs-CRP levels increased significantly with CAD severity (2.4 ± 0.9 mg/L in mild, 4.6 ± 1.1 mg/L in moderate, and 6.8 ± 1.5 mg/L in severe CAD; p < 0.001). Patients with severe CAD also had significantly higher fasting blood glucose, HbA1c, total cholesterol, LDL, triglycerides, and serum creatinine, and lower HDL levels compared to those with mild disease (all p < 0.05). Male predominance, older age, longer diabetes duration, higher BMI, and hypertension were more common in patients with advanced CAD. Conclusion: Elevated hs-CRP levels show a strong and independent association with angiographic severity of CAD in patients with T2DM, supporting the role of systemic inflammation in diabetic atherogenesis. hs-CRP may serve as a valuable adjunctive biomarker for cardiovascular risk stratification in diabetic individuals undergoing CAD evaluation. Keywords: Type 2 diabetes mellitus, Coronary artery disease, hs-CRP, Inflammatory biomarkers, Atherosclerosis, Angiography, Cardiovascular risk, Glycemic control